Priority Analysis of Green Open Space in Pekanbaru City - Umara Hasmarani Rizqiyah; Nizar Nasrullah; Bambang Sulistyantara (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Pekanbaru City Government issued a letter of interest to the central government regarding the Letter of Interest in Participating in the Green City Development Program (P2KH). One of the attributes of P2KH is Open Green Space. In 2020, when referring to the Spatial Planning Law, Pekanbaru City should have 12,780,31 ha of green open space to meet the figure of 30% of the city area. However, currently Pekanbaru only has 3,195.08 ha of green open space, which consists of green lanes, cemeteries, city parks, urban forests, and road median parks. Pekanbaru's green open space is becoming increasingly depleted, making the Pekanbaru City government plan to change the city concept to a "City in a Garden", and this will be pursued until 2024. The location for further green open space can be identified to be more effective in reducing temperatures in Pekanbaru City. This priority area analysis was carried out using USGS image data and Geographic Information System (GIS) processing. The calculated data are NDVI, Surface Temperature (LST), Air Temperature, Relative Humidity (RH), and also the THI thermal comfort index for the people of Pekanbaru City.